Therapist´s personal style of psychologists in intellectual disability work - Casari, Leandro Martín (2022)
The objective of this article is to describe the Therapist´s Personal Style (TPS) in clinicalpsychologists who work with patients with intellectual disabilities, and to analyse theeffect of the theoretical approach and the years of professional experience. This researchwas conducted on a group of 104 psychotherapists from Argentina divided into two equalgroups: 52 who work with people with intellectual disabilities and 52 who work withthe general clinical population in private practice. As a result, significant differenceswere found in three dimensions of the TPS: Operative, Involvement, Expressive, whichobtained higher scores in the first group of therapists. The theoretical approach did notshow a differential effect on the therapist groups except for the Expressive function,and a significant difference was found in years of professional experience in intellectual disability therapists. These results are discussed with previous research and theimportance of studying the profile of therapists is reflected upon.